Modification of the Upper Limb Functional Index to a Three-point Response Improves Clinimetric Properties - Gabel, C.; Michener, L.; Melloh, Markus; Burkett, B. (Elsevier, 2010)
Study Design: Observational two-stage. Introduction: To achieve optimal clinimetric properties for outcome measures, both practical and psychometric, ongoing improvements are required. Purpose of the Study: To evaluate if the Upper Limb Functional Index (ULFI) clinimetric properties are improved by modification to a three-point response option and to verify the factor structure. Methods: Stage 1, calibration (n = 139) used ULFI dichotomous responses, and stage 2, validation (n = 117) used a three-point response option. The clinimetric properties were compared in physical therapy outpatients with the QuickDASH as the reference standard. Repeated measurements were made at two to four weekly intervals. Results: The ULFI three-point response option improved reliability [intraclass correlation coefficient (2,1) = 0.98], internal consistency (a = 0.92), QuickDASH concurrent validity (r = 0.86), and responsiveness. Minimal detectable change (90% confidence interval) was 7.9%, and factor structure was unidimensional. Missing responses were <0.5%, and practical characteristics were unchanged. Conclusions: The enhanced reliability and reduced errors with unchanged practicality demonstrate the ULFI improvements through modification to a three-point response option. Level of Evidence: 2c. Crown Copyright © 2010.